Partial purification of topoisomerase IB from serum of diabetic patients and study it's kinetic properties and molecular weight - Saif M. Hasan; Firas T. Maher; Nagham Q. Kadhim (Tikrit Journal of Pure Science)
This study was done to partially purification of  topoisomerase IB from serum of diabetic patients using Gel filtration technique, by using Sephadex G 100 gel. A single peak in fraction four has been obtained, and the degree of purification (17.1) fold, enzyme yield (108.2%) and specific activity (0.189ng/mg). Kinetics studies for the partial purified enzyme were carried out which showed optimal concentration of  substrate which was (0.1ng/ml), Michael's - Menten constant (Km=0.033ng) and maximum velocity (Vmax=0.90 ng/ml), while optimum Temperature was (37C°) and optimum pH was (7.5). The molecular weight of the partial purified enzyme has been determined by gel electrophoresis method, in presence of polyacrylamide  gel and sodium dodecyl sulphate (SDS-PAGE) which showed that the approximated molecular weight was (66KD).